PENGARUH PENDELEGASIAN WEWENANG DALAM MENINGKATKAN EFEKTIFITAS KERJA PEGAWAI PADA BADAN PUSAT STATISTIK KABUPATEN OKU TIMUR - Titie Syahnaz Natalia; Dyah Ayu Putriani (Jurnal Manajemen Bisnis Unbara, 2022)
Abstract Based on the results of data analysis, there is a positive influence between the Delegation of Authority to Improve the Work Effectiveness of Employees at the Central Bureau of Statistics of East OKU Regency. This shows that with good delegation of authority, it will lead to work effectiveness and this has a positive impact on employees of the Central Bureau of Statistics of East OKU Regency. As for what has been described above, it is explained that the Delegation of Authority affects the effectiveness of the work of the Central Statistics Agency of East OKU Regency, it is proven by using the t test, the value of T_hitung 10,598 > T_table 2,059 means that the Delegation of Authority affects work Effectiveness. Keywords : Delegation Of Authorities, Effectiveness Of Employess.